PERAN SYEKH MUHAMMAD ARSYAD AL-BANJARI DALAM PENYEBARAN ISLAM DI TANAH BANJAR - Abdul Wahab Syahrani; Erfan Alfian (Cross-border, 2022)
Banjar people during Arsyad's time tended to believe in animism and dynamism that influenced the Banjarese before, so many still believed in the occult. This tendency can be seen in the presence of people who hold ceremonies asking for blessings, help and success by placing offerings on trees that are considered sacred and inhabited by supernatural beings, so that the teachings of Islam have not been fully applied in the daily life of Sheikh Muhammad Arsyad al -Banjari (later called Arsyad) is a historical actor who spread Islam.